2014
DOI: 10.1103/physreva.89.052323
|View full text |Cite
|
Sign up to set email alerts
|

Creating and manipulating entangled optical qubits in the frequency domain

Abstract: Radio-frequency phase modulation of frequency entangled photons leads to a two-photon interference pattern in the frequency domain. In recent experiments, the pattern was measured with narrow-band frequency filters which select photons belonging to a given frequency bin. Here we show how photons can be grouped into even and odd frequencies by using periodic frequency filters called interleavers. In our theoretical analysis we show how this reduces the high-dimensional photon state to an effective two-dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The quantum optics experiment follows closely that reported in [28] (except for the frequency filters that are of the type used in [27]). In detail, a continuous-wave laser (from Sacher Lasertechnik) with wavelength λp = 2πc/ωp = 776.04 nm pumps a periodically-poled lithium niobate waveguide (from HC Photonics), thus generating frequency-entangled photons around wavelength λ 0 = 2πc/ω 0 = 1552.08 nm.…”
Section: Measurement Of Frequency-bin Entanglementmentioning
confidence: 67%
See 2 more Smart Citations
“…The quantum optics experiment follows closely that reported in [28] (except for the frequency filters that are of the type used in [27]). In detail, a continuous-wave laser (from Sacher Lasertechnik) with wavelength λp = 2πc/ωp = 776.04 nm pumps a periodically-poled lithium niobate waveguide (from HC Photonics), thus generating frequency-entangled photons around wavelength λ 0 = 2πc/ω 0 = 1552.08 nm.…”
Section: Measurement Of Frequency-bin Entanglementmentioning
confidence: 67%
“…After subtraction of the background noise, large net visibilities are obtained, see table 1. As shown in [26][27][28], frequency-bin entanglement can be used to violate the Clauser-Horne Bell inequality, by a theoretical maximal value of S = 2.389. Measured visibilities should allow a violation of at least 2.2.…”
Section: Quantum Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The recent progress in the generation and manipulation of OAM has led to the demonstration of OAM qubits and entanglement of the orbital angular momentum states of photons [33]. Frequency qubits can also be created by using a superposition of basic states at frequencies ω 1 and ω 2 , as it is done with atoms; this approach has not been well developed yet, mainly because of the difficulty in chosing arbitrary measurement basis for frequency, nevertheless we can cite some interesting experimental works recently done with these qubits [34,35].…”
Section: Photonic Qubitsmentioning
confidence: 99%
“…It has been shown that photons from different frequencies interfere at the single quantum level (13) and that such two-parties system can violate Bells inequalities (14). However, such studies do not allow quantum logic operations in a 2-dimensional Hilbert space, and a more complex definition of a frequency-encoded qubit is required (15) to realize this ideal case. The core of our work is the efficient and low-noise frequency conversion of single photons that was proposed 2 decades ago (16) and for which various successful studies using χ (2) and χ (3) nonlinear interactions have been demonstrated (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%